Mekanisme Hipotetikal Efek Konsumsi Ikan Menurunkan Resiko Serangan Jantung - I Dewa Ayu Susilawati (STOMATOGNATIC - Jurnal Kedokteran Gigi, 2018)
Potential maritime Indonesia related health science has not been widely explored. Studies in Indonesia about the potential of marine resources to improve health are still very little. This article summarized a reports from magazines and journals in foreign countries about the potential fish consumption lowers the risk of heart attack. Allegedly this potential is related to the content of unsaturated fatty acids omega-3 (n-3) on fish. The report of observations, clinical , animal and in vitro studies have demonstrated the benefits of omega-3 prevent and treat cardiovascular disease. Although the mechanism is not clear, but it has been shown that the cardioprotection effect of n-3 fatty acids may be caused by its role influencing biological effects on lipid and lipoprotein metabolism, platelet function, arterial cholesterol distribution, vascular function and inflammatory response